The Legal Consciousness and Social Impacts of the Change in the Minimum Age for Marriage in the Indonesian Marriage Act: The Experience of Hulu Sungai Tengah, Kalimantan Selatan - Tavinayati Tavinayati; Varinia Pura Damaiyanti; Lena Hanifah; Ayesha Wijayalath; Trisna Putri; Galuh Fitria Rizqyandhanita (Scholar Center, 2022)
Child marriage is still a controversial and big challenge that Indonesia has always faced, with Kalimantan Selatan as one of the Big Five Provinces with the highest number of child marriages. The Indonesian government has taken various preventive steps, one of which is revising the age limit for brides from 16 to 19 years old, enacted right before Covid-19 hit the country. However, the revision still begs questions about whether the age limit is practical due to the highest number of unregistered marriages, especially during the pandemic. This study employed the Qualitative method with a Socio-Legal approach and found that the perception and legal consciousness of the respondents were undisputed towards child marriage and disregarded the age limit and the pandemic situation.